2016
DOI: 10.4278/ajhp.141027-lit-542
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Approaches to Occupational Health and Safety: A Systematic Review

Abstract: Integrated approaches have been posed as comprehensive solutions to complex issues. Empirical evidence, while still emerging, provides some support for this. Continuing investment in, and evaluation of, integrated approaches are worthwhile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 47 publications
2
45
0
3
Order By: Relevance
“…This work builds on growing evidence about the potential benefits of integrated approaches for improvements in health behaviors (Bertera, 1990, 1993; Elliot et al, 2007; Maes et al, 1998; Okechukwu et al, 2009; Olson et al, 2009; Sorensen et al, 2005; Sorensen et al, 2007; Sorensen et al, 1998; Sorensen et al, 2002); enhanced rates of employee participation in programs (Hunt et al, 2005); potential reductions in pain, occupational injury and disability rates (Hlobil et al, 2007; Pronk et al, 2012; Robertson et al, 2013; Shaw et al, 2006; Shaw et al, 2003; Tsutsumi et al, 2009); strengthened health and safety programs (Goetzel et al, 2001; LaMontagne et al, 2004); potentially reduced costs (Goetzel et al, 2001); and support for market performance of companies (Fabius et al, 2016; Malan et al, 2009). These findings are supported by multiple reviews of integrated interventions (Anger et al, 2015; Cherniack, 2013; Cooklin et al, in press; Goetzel, 2012; Institute of Medicine Committee to Assess Worksite Preventive Health Program Needs for NASA Employees, 2005; National Institute for Occupational Safety and Health, 2012; Pronk, 2013; Sorensen et al, 2011a), although a recent systematic review concluded that while integrated interventions may improve health behaviors, there remains a significant need for further evidence on their impact on injuries and overall quality of life (Feltner et al, 2016). …”
Section: Introductionsupporting
confidence: 58%
“…This work builds on growing evidence about the potential benefits of integrated approaches for improvements in health behaviors (Bertera, 1990, 1993; Elliot et al, 2007; Maes et al, 1998; Okechukwu et al, 2009; Olson et al, 2009; Sorensen et al, 2005; Sorensen et al, 2007; Sorensen et al, 1998; Sorensen et al, 2002); enhanced rates of employee participation in programs (Hunt et al, 2005); potential reductions in pain, occupational injury and disability rates (Hlobil et al, 2007; Pronk et al, 2012; Robertson et al, 2013; Shaw et al, 2006; Shaw et al, 2003; Tsutsumi et al, 2009); strengthened health and safety programs (Goetzel et al, 2001; LaMontagne et al, 2004); potentially reduced costs (Goetzel et al, 2001); and support for market performance of companies (Fabius et al, 2016; Malan et al, 2009). These findings are supported by multiple reviews of integrated interventions (Anger et al, 2015; Cherniack, 2013; Cooklin et al, in press; Goetzel, 2012; Institute of Medicine Committee to Assess Worksite Preventive Health Program Needs for NASA Employees, 2005; National Institute for Occupational Safety and Health, 2012; Pronk, 2013; Sorensen et al, 2011a), although a recent systematic review concluded that while integrated interventions may improve health behaviors, there remains a significant need for further evidence on their impact on injuries and overall quality of life (Feltner et al, 2016). …”
Section: Introductionsupporting
confidence: 58%
“…After removing duplicates, 321 were manually screened, and 286 records were excluded for title and abstract. We reviewed the full text of 35 studies, 24 of which were excluded [11,12,14,18,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Finally, eleven SRs were included in the narrative synthesis ( Figure 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Lack of time for the eyes to rest can cause various diseases. The eye is one of the most sensitive and vulnerable parts of the disease from outside [2], [10]. Other results indicate that the distance of the monitor to the eye and sitting position also as the main cause of OHS related diseases on the computer.…”
Section: Fig 2 Percentage Of Types Of Employees' Urgent Issues Relamentioning
confidence: 99%
“…The results showed that the greatest percentage occurred in headache-comp disease resicons (85%). This disease is a disease with tenderness of muscle tension headache and is the most common type [2], [15]. This disease has symptoms of headaches on both sides of the head, it is suppressing, sometimes feels heavy with constant dull pain.…”
Section: Risks Of Illness Suffered By Employees Related To Computer Ohsmentioning
confidence: 99%
See 1 more Smart Citation